Dinamika Urbanisasi dan Perubahan Elemen Ekistik: Studi Kasus Kota Surakarta - Astita, Sarah (UI Scholars Hub, 2025)
Urbanization has become a driving force behind significant spatial, environmental, and socio-economic transformations in urban areas, including Surakarta, the most densely populated city in Central Java. The rapid increase in population and urban expansion has led to drastic changes in land use and the structure of human settlements. This study aims to analyze the impact of urbanization on the ekistic elements of Surakarta (nature, humans, society, space/shells, and networks) and how these changes manifest spatially over time. A descriptive qualitative approach is employed using literature analysis and the interpretation of Landsat satellite imagery from 2011 and 2022. The findings show a notable decline in agricultural land and green open spaces, accompanied by a significant increase in built-up areas and public facilities. Transportation networks have also expanded to accommodate growing mobility demands. Among the five ekistic elements, nature, space, and networks are the most affected, responding directly to the spatial needs of a growing urban population. Meanwhile, the elements of humans and society are indirectly influenced through changes in infrastructure and the environment. This research highlights the importance of integrating the ekistics framework into urban planning to better understand and manage the complex dynamics of urban growth. The study offers valuable insights into how urbanization shapes city form and function, and provides a foundation for sustainable development strategies in rapidly urbanizing regions